Snakebite profile from a tertiary care setup in a largely rural setting in the hills of North-West India - Anil Kumar (Journal of Family Medicine and Primary Care, 2021)
Background: Snakebite, a medical emergency, faced by rural populations in tropical and subtropical countries assumes special significance in hilly terrains. Therefore, the hills provide a natural setting to study the challenges in the management of snakebite cases. Methodology: A hospital record-based retrospective descriptive study was conducted. Data were collected from the Medical Records Department of the 821-bedded, tertiary care hospital catering to the rural hilly population of the state of Himachal Pradesh, India. Information were recorded on details of demography, clinical profile treatment and outcome. Results: A total of 252 patients were analyzed. Maximum patients were in the age-group of 21–40 (43.7%) with mean and standard deviation of 30.52 ± 5.693 and 31.81 ± 7.117 for male and female, respectively. A small minority (17.06%) of patients reported to health facility within 4–6 h of the bite. Maximum bites were on lower limb (143;56.74). Overall mortality rate in our study was 2.38%. Conclusion: Large-scale studies on epidemiological determinants of snakebite coupled with research in venom biochemistry and bio-pharmacology of anti-snake venom (ASV) are needed. The study also provides insights into the role of primary care practitioners in creating an ecosystem favorable for snakebite management at local level.